Autobiographical narratives in the elderly with neurocognitive disorder: an integrative literature review - Ana Paula Machado Goyano Mac-Kay; Melissa Barrera; Camila Córdova; Romina Olivares; Daniela Vásquez (Revista CEFAC, 2020)
ABSTRACT Objective: to carry out an integrative review of the literature on autobiographical narratives as a discursive activity in the older adult with neurocognitive disorder. Methods: a descriptive study that covered the Scopus, SciELO, PubMed, and Science Direct databases, from 2009 to 2019, using the keywords autobiographical, narrative, dementia, reminiscence, the elderly, and the Boolean operator. A narrative synthesis was adopted considering the characteristics of the clinical, and methodological heterogeneity of the studies. Results: the results included 3 articles published between 2012 and 2018, in the English language, from the United Kingdom, Brazil, and Argentina, which highlighted the autobiographical narratives. Although in a strict sense they did not present the narrative as a specific objective of the autobiographical study, they did provide interesting and related data which justified their inclusion. Conclusion: it is observed that the literature researched presents a limited number of articles, adressing the autobiographical narrative as a discursive activity in the elderly with neurocognitive disorder.